KONTRIBUSI STATUS GIZI DENGAN HASIL BELAJAR PENJASORKES SISWA PUTERA KELAS V SDN 002 KINALI KECAMATAN KUANTAN MUDIK - Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the result of learning penjasorkes students are still many who do not reach the target (KKM). This is presumably because the nutrition status of being owned students. Therefore, the purpose of this study was to determine whether there is a contribution nutrition status with penjasorkes learning outcomes class V male students of SDN 002 Kinali District of Kuantan Mudik. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is a nutritional status of male students class V SDN 002 Kinali District of Kuantan Mudik while the dependent variable (Y) is the penjasorkes learning outcomes class V male students of SDN 002 Kinali District of Kuantan Mudik. Based on the research that has been done on male students in class V SDN 002 Kinali District of Kuantan Mudik to determine the extent of the contribution of nutrition status with penjasorkes learning outcomes class V male students of SDN 002 Kinali District of Kuantan Mudik obtained rhitung (0.51)> rtabel (0,482). Then it can be concluded as follows: There is contributing nutrition status with penjasorkes learning outcomes class V male students of SDN 002 Kinali District of Kuantan Mudik with a contribution of 26.01%.Keywords : Nutrition Status, Learning Outcomes, Penjasorkes